Application of blended fuel containing coffee ground pyrolysis oil in a diesel generator. (15th November 2019) - Lee, Seokhwan; Choi, Young; Kang, Kernyong
Highlights: We investigated the possibility of direct use of coffee ground pyrolysis oil in a diesel engine. The auto-ignition properties of the blended fuels can be enhanced by two cetane improvers. The efficiency of the blended fuels was slightly higher than that of diesel. The PM emissions from blended fuels were significantly reduced. Abstract: The combustion and emission characteristics of blended fuel composed of coffee ground pyrolysis oil (CGPO), n-butanol and cetane enhancements were investigated in a diesel generator. CGPO, which can be obtained from spent coffee grounds by a fast pyrolysis process, has attracted interest due to its potential application as an alternative fuel. However, CGPO cannot be used in diesel engines directly without causing problems such as clogging the fuel supply equipment and misfiring due to the poor properties of the fuel. Generally, the polymerization of pyrolysis oil could be prevented by diluting it with alcohol fuels. Additionally, CGPO should be enhanced with cetane improver because it does not self-ignite. In this study, CGPO was blended with n-butanol and two cetane improvers. Engine bench test results showed that engine operation was highly stable using blended fuel. Although the carbon monoxide (CO) and nitrogen oxides (NOx) emissions of the blended fuels were larger than those of diesel, the hydrocarbon (HC) and particulate matter (PM) emissions decreased due to the high oxygen content of n-butanol and CGPO.